Criminal liability of the middle managers and corporate crimes - Chanjan Documet, Rafael Hernando (2016)
Corporate crimes have become a highly widespread phenomenon in modern industrialized societies. The aim of this paper is to offer criteria and elements to evaluate criminal liability of middle managers of a highly hierarchical company for criminal acts committed by employees, which have been adopted and conceived by top managers of the company. To this end, different theories that have arised from the criminal doctrine to penalize managers of a complex organization will be analyzed, as truemediate authorship, co-authorship, induction and authorship in the omission. The research is justified to the extent that, criminal doctrine and jurisprudence, haven’t analyzed this issue deeply and, in the few opinions that about it exist, there are discrepancies about it possible solution.